An investigation of entrepreneurial orientation and organisational strategies in Chinese SMEs. (8th November 2010) - Tang, Zhi; Tang, Jintong; Marino, Louis D.; Zhang, Yuli; , Qianwen Li
This paper attempts to enhance our understanding of entrepreneurship in China by addressing two research questions: 1) Can entrepreneurship in China be understood through the constructs (e.g., entrepreneurial orientation) developed in Western cultures?; 2) Do entrepreneurial firms in China employ the same strategies as their Western peers do? We conducted two studies to examine the validity of Miller's original scale of entrepreneurial orientation (EO) in the Chinese context and to investigate the relationships between EO and organisational strategies. Results indicate that the EO measure is psychometrically valid when applied in China. Further, innovation strategy is commonly adopted to compete in the market place, while cost-saving is not a significant strategic option.